KRAS mutational status impacts pathologic response to pre-hepatectomy chemotherapy: a study from the International Genetic Consortium for Liver Metastases. Issue 11 (November 2019) - Margonis, Georgios A.; Amini, Neda; Andreatos, Nikolaos; Sasaki, Kazunari; McVey, Jack; Mirza, Muhammad B.; Warner, Samuel; Buettner, Stefan; Barbon, Carlotta; Wang, Jane; Pulvirenti, Alessandra; Angelou, Anastasios; et al.
Abstract: Background: A major response to pre-hepatectomy chemotherapy has been associated with improved survival in patients who undergo resection of colorectal liver metastases (CRLM). However, the role of tumor biology, as exemplified by overall and codon-specific KRAS mutational status, in predicting response to chemotherapy is not well defined. Methods: Pathologic response was characterized as minor or major depending on the percentage of remnant viable cells (>50% vs <50%, respectively). Multivariable logistic regression was used to identify factors associated with major response. Results: 319 patients met inclusion criteria. 229 patients had a KRAS wild-type (wtKRAS) tumor and 90 harbored KRAS mutations (mutKRAS). A major pathologic response was more commonly noted in patients with wtKRAS compared to mutKRAS (48.5% vs 33.3%, P = 0.01) and wtKRAS status remained independently associated with a major response (P = 0.04). On a codon-specific level, major pathologic response occurred less frequently in those with codon 13 mutations (17.7%) compared to those with codon 12 (35.4%), and other KRAS mutations (33.3%). Importantly, codon 13 mutations were independently associated with minor pathologic response (P = 0.023). Conclusions: Patients with wtKRAS tumors appear to have the highest likelihood of experiencing a major response after preoperative chemotherapy. Future studies in "all-comer" cohorts are needed to confirm these findings and further investigate the response of codon 13 mutations.